International business in times of crisis - Tulder, Rob van; Verbeke, Alain; Piscitello, Lucia; Puck, Jonas (Progress in international business research ;, 2022)
This sixteenth volume in the PIBR series, International Business in Times of Crisis, is dedicated to Professor Geoffrey Jones from the Harvard Business School, and to the importance of historical scholarship in International Business (IB) studies. The global Covid-19 crisis triggered a profound economic crisis, with a decline in global economic activity on a scale not seen since the Great Depression. This pandemic revealed systems failures and fragilities closely related to the organization of global economic, financial, political, and social systems. It has confronted the world with fundamental questions regarding how the global community, as well as companies in general and multinational enterprises (MNEs) in particular, should design global responses to crises. A multi-level and longitudinal approach to studying crises in IB is clearly necessary. This book classifies studies of crises relevant to IB research and will hopefully be helpful to IB scholars, as they reflect on the type of crises they want to study as part of their future research agenda. "The main point coming out of this brief description of my own intellectual journey is to emphasize that crises have been the norm rather than the exception in the history of international business. They have taken many forms and building a typology of crises would be a helpful next step in new research." Geoffrey Jones (in this volume).